Rebel Science - Dan Green (London Weldon Owen Publishing, 2014)
From ground-breaking discoveries to disastrous dead-ends, science isn't always, well . . . scientific. Without some catastrophic mess-ups, the world might never know modern marvels, miraculous medicines, magnificent machines and much more. This dynamically illustrated book brings to life the rebel scientists who stuck out their necks to achieve our greatest leaps forward, and uncovers the shocking truth about the biggest blunders - and most unexpected successes - ever to happen in the lab.